2022
DOI: 10.3390/foods11223570
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach in the Baking of Bread with CO2 Gas Hydrates as Leavening Agents

Abstract: Gas (guest) molecules are trapped in hydrogen-bonded water molecules to form gas hydrates (GH), non-stoichiometric solids that resemble ice. High pressure and low temperature are typical conditions for their development, with van der Waals forces joining the host and guest molecules. This article study investigates the application of CO2 gas hydrates (CO2 GH) as a leavening agent in baking, with particular reference to the production of wheat bread. The main intention of this study is to better understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It was discovered that the standard made with yeast, EW, and RF had significantly more browning than the other standard bread made only with EW and RF or the standard made with AC, EW, and RF. The reason might be attributed to the fact that yeast impacts bread color by producing secondary metabolites via several metabolic pathways via non-enzymatic chemical processes such as Maillard and caramelization [ 21 , 22 , 23 ], which generate brown colored chemicals during baking [ 24 , 25 , 26 ]. Moreover, it was found that the addition of 40% GH in the wheat bread along with gelling agents AC, EW, and RF further enhanced the physical appearance of the bread in comparison to the standards that were made alone with EW and RF or AC, EW, and RF combinations ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was discovered that the standard made with yeast, EW, and RF had significantly more browning than the other standard bread made only with EW and RF or the standard made with AC, EW, and RF. The reason might be attributed to the fact that yeast impacts bread color by producing secondary metabolites via several metabolic pathways via non-enzymatic chemical processes such as Maillard and caramelization [ 21 , 22 , 23 ], which generate brown colored chemicals during baking [ 24 , 25 , 26 ]. Moreover, it was found that the addition of 40% GH in the wheat bread along with gelling agents AC, EW, and RF further enhanced the physical appearance of the bread in comparison to the standards that were made alone with EW and RF or AC, EW, and RF combinations ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the previous studies in this area of GH as a leavening agent showed that GH alone was not sufficient enough to make the bread softer in texture as it was in this case. The amount of hardness in the bread made with GH was a major concern when GH was added alone as a leavening agent [ 21 ]. The major strategy for resolving the issue raised in the previous research pertaining to the hardness of the GH bread is to blend certain functional gelling agents, to partially simulate wheat bread properties [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations